The Role of Critical Success Factors in Strategic Implementation: An Analytical Study of the Opinions of a Sample of Department Heads in Private University Colleges in Erbil, Kurdistan Region, Iraq. - ابراهيم ولي, احلام; مصطفى عبدالله, هاوبەش (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The aim of the research is to diagnose the critical success factors in private universities in the city of Erbil, represented by (information technology, senior management support, employee empowerment) and analyze their relationship and impact on the dimensions of strategic implementation within the framework of the analysis of the McKinsey model for strategic implementation, represented by (strategy, structure, systems, administrative styles, common values, skills, individuals). The general framework of the research is represented by the intellectual problem, which raised several questions about the nature of the relationship and influence between the independent variable (critical success factors) and the dependent variable (strategic implementation). Questionnaire form as the main tool for obtaining data. The research followed the analytical descriptive approach, as the main and secondary variables were described, as well as the relationships and influence between the variables were analyzed. As for the research sample, they numbered (136) members, as the percentage of the sample was(39.1%) from the community, which is sufficient for analysis in the humanities. The hypotheses were tested through a set of statistical tests by the computer program (SPSS V.23). The research reached a set of conclusions, the most important of which is the presence of high correlations and strong effects between the main and sub-variables, at the macro and micro levels. The research suggested a set of proposals in the light of the conclusions, including the necessity of harnessing the strong relationships between the two variables and directing them towards serving the universities under study.